Causes of Endodontic Failure and Remedies - K, NIRUBAMA.; K, ANJANEYULU.; D, EZHILARASAN. (The journal of contemporary issues in business and government, 2021)
The ultimate goal of any endodontic treatment is to provide a correct diagnosis, optimal mechanical and chemical preparation, and to three-dimensional obturation of the root canal. Persistence of microorganism like bacteria in the apex and canals, poor obturation quality, over and under an extension of the root canal filling, inappropriate mechanical debridement, and coronal leakage noted as come of the commonly attributable causes of failure. Review of literature by collecting and retrieving information from a minimum of 47 articles. Articles were retrieved from search engines such as PubMed, Google Scholar, etc. Despite the high success rate regarding the endodontic treatment, failures also occur in a large no. of cases. The failures that occur most of the time can be attributed to the previously mentioned causes. Since several endodontic treatments are done every day, it has become essential to minimize or avoid the most fundamental of reasons leading to endodontic failure. This paper reviews and highlights the most common causes of endodontic failure.